(3GdETGQI Edi JMSjf GdYHGQIs - (3Ydj Hf aqVGd Hf Ydj Hf ZGdH GdeLGTYj GdbjQhGfj GdaQRObj , CHh GdMSf,J (B479 (3g` s ((3eMeO Hf Ydj GdfSGL s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg MeOkG jRda dOjg aEfj LeYJ aj gPG GdcJGH CHhGHkG ef GdEYQGH jUZQ MLegG, hjcKQ YdegG s
(3BNQgG (B:s
(3aCeG ef jcJH Ydi Bdg adjS HeUjH, dCf GdeVeQ Hg jQO GdTF Edi CUdg, hCUd Bd Cgd hHGddg GdJhajb BNQ GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GdfSNI HgG MhGTs
(3NW eged GdfbW bdjdkG ajg VHWs
(3hbO fSNgG ef fSNI ecJhHI ef fSNI GdEeGe CHj GdMSf Hf YHOGdZGaQ GdJj bQCgG Ydi eUfag s
(3Ydi MhGTjgG fbhd ef cJGH GdEcSjQ ddeUfa faSgs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
Keywords: (3GdfMhs